Blunt Isolated Small Bowel Perforation Intervention: Does a Delay in Management Matter? - Sung Yong Hong; Se Hun Kim; Ki Hoon Kim (Emergency Medicine International)
Purpose. Blunt small bowel injury is rare, and its timely diagnosis may be difficult. The effects of a delayed intervention on prognosis are unclear. We aimed to determine whether the time to surgical intervention affects outcomes in patients with blunt small bowel perforation. Methods. The study was performed between March 2010 and December 2018 in adults (age >18 years) who initially underwent computed tomography and small bowel surgery only and survived more than one day postoperatively. They were categorized into three groups based on injury-to-surgery time intervals: ≤8, 8–24, and >24 h; similarly, they were also categorized into two groups of ≤24 and >24 h. Results. Bowel resection, length of stay (LOS), intensive care unit (ICU) LOS, morbidity, and mortality were analyzed as outcomes in 52 patients. The number of patients in the three groups (≤8, 8–24, and >24 h) based on the time-to-surgery was 33, 13, and 6, respectively. On comparing the three groups, there were no significant differences in LOS (24 [18–35], 21 [10–40], and 28 [20–98] days, respectively; p=0.321), ICU LOS (2 [1–12], 4 [2–26], and 11 [7–14] days; respectively, p=0.153), mortality (3% (n = 1), 15% (n = 2), and 0%, respectively; p=0.291), and morbidity (46% (n = 15), 39% (n = 5), and 50% (n = 3), respectively; p=0.871). However, there was a significant difference between the groups in bowel resection (67% (n = 22), 31% (n = 4), and 83% (n = 5), respectively; p=0.037). Additionally, there was no significant difference in outcomes between the two groups (≤24 and >24 h) with small bowel perforation. Conclusions. Delay in surgical intervention following blunt abdominal trauma may not affect the outcomes of patients with small bowel injuries, such as LOS, ICU LOS, morbidity, and mortality, except bowel resection.